Implementasi Wajar Dikdas di Pondok Pesantren Salafiyah - Anita, Dewi Evi (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2016)
AbstrakEducation has a role in feeding the nation, either through formal or non formal education. Since 2000 the Government announced compulsory primary education in boarding schools, with first consideration Salafi students boarding schools Salafiyah is the compulsory age students. Second, it is expected students after graduation from boarding schools Salafi have an equal chance in gaining employment. Consideration of the annual programme of Wajar Dikdas in boarding schools Salafiyah APIK Kaliwungu and Darul Falah Jekulo Kudus based on mutual agreement between the Minister of religious affairs with the Minister of national education, about the Government programs to complete compulsory primary education in boarding schools Salafi, due to quantity the number of boarding schools Salafiyah very much, mostly located in rural areas and yet affordable by institutions of formal education or not evenly education, the high number of drop outs, pessimism urgensitas against education for community life and future students. Wajar Dikdas program at the boarding schools Salafiyah APIK Kaliwungu and Darul Falah Jekulo Kudus is not a primary education at both the boarding schools.Keywords: Pondok Pesantren Salafiyah, Wajib Belajar Pendidikan Dasar